Caloric restriction counteracts chemotherapy-induced inflammation and increases response to therapy in a triple negative breast cancer model. Issue 13 (3rd July 2018) - Simone, Brittany A.; Palagani, Ajay; Strickland, Kimberly; Ko, Kevin; Jin, Lianjin; Lim, Meng Kieng; Dan, Tu D.; Sarich, Mak; Monti, Daniel A.; Cristofanilli, Massimo; Simone, Nicole L.
ABSTRACT: Triple negative breast cancer (TNBC) is a heterogeneous disease that has no available targeted therapies. Previously, we have shown that caloric restriction (CR) can augment the effects of radiation therapy in a TNBC mouse model. To build upon this, we now present data regarding the combination of chemotherapy and CR in the same 4T1 model. Chemotherapy can induce inflammation that breeds resistance to therapy. We propose CR as a mechanism to decrease chemotherapy-induced inflammation and increase efficacy of therapy. 12-week old Balb/c mice were orthotopically injected with a syngeneic triple negative breast cancer cell line (4T1) and were treated in one of six cohorts: ad lib fed (AL), 30% reduction in calorie intake (CR), cisplatin or docetaxol alone or a combination CR+cisplatin/docetaxol. Mice in the cohorts receiving chemotherapy+CR had longer overall survival (12 ± 2 days) as compared to the AL group. These mice also demonstrated less lung metastases at the final time point of in vivo imaging. In addition, downregulation of the IGF-1R and IRS signaling pathways were noted most significantly in those mice receiving combination therapy. Lastly, serum from these mice demonstrated an increase in inflammatory cytokines TNF-α and IL-1β in response to chemotherapy alone. This increase was dampened by the addition of CR. Taken together, these data suggest that while chemotherapy is effective in TNBC, it can cause inflammation, which can be a driver of resistance to therapy. This chemotherapy-induced inflammation can be reversed with the use of CR as a nontoxic adjunct to treatment.